Physical and numerical modelling of ground-borne vibrations in sand - Cui, Ge (2020)
The problems caused by urban congestion and population growth result in a growing need to construct railway networks in urban areas due to the advantages of safety, efficiency and reliability over alternative mass transportation options. However, railway systems can cause environmental issues due to the transit of vehicles, including railway noise and vibration. The problem of ground-borne vibration has gained increasing attention because people are becoming less likely to tolerate environmental disturbance and sensitive buildings and equipment could be significantly affected by nearby groundborne vibrations. Therefore, it is necessary to investigate those effects and provide a better understanding of ground-borne vibrations from railways. This research work was primarily concerned with the transmission of vibration from railways via a single friction pile through the soil-pile interface and the ground.